Annual FEV1 Loss in Patients with Noncystic Fibrosis Bronchiectasis and Affecting Factors. Issue 5 (May 2022) - Borekci, Sermin; Gundogdu, Sule; Harbiyeli, Deniz Ongel; Musellim, Benan
Abstract : Bronchiectasis is a chronic respiratory disease characterized by sputum production, cough, and several bronchial infections. Lung function is an important parameter to evaluate and study in patients with bronchiectasis. This study aimed to evaluate the annual changes in lung function tests/spirometric parameters and related factors in patients with with noncystic fibrosis bronchiectasis. A total of 153 patients were included in the study, in which an annual mean forced expiratory volume in 1 second (FEV1 ) loss of 39 mL was found in adult patients with noncystic fibrosis bronchiectasis. The annual mean FEV1 decline was found to be associated with the baseline FEV1 value. Physicians should exercise caution in this regard in patients with bronchiectasis with low FEV1 values. Abstract: Objectives: Bronchiectasis is a chronic respiratory disease characterized by sputum production, cough, and several bronchial infections. Lung function is an important parameter to evaluate and study in patients with bronchiectasis. This study aimed to evaluate the annual changes in forced expiratory volume in one second (FEV1 ) and related factors in patients with with noncystic fibrosis bronchiectasis. Methods: A total of 529 patients who were diagnosed as having bronchiectasis using computed tomography and followed at the bronchiectasis unit of the Cerrahpasa Medical Faculty at Istanbul University between 1996 and 2018 were included in this retrospective study. A total of 153 patients were included in the study. Results: The mean age of the patients was 58.6 ± 16.8 years and 61% (n = 93) were female. The annual change of FEV1 and forced vital capacity was −39 ± 82 (minimum: −585, maximum: 355, median: −26) mL and − 44 ± 91 (minimum: −517, maximum: 303, median: −31) mL, respectively. There was no correlation in FEV1 decline between those with and without Pseudomonas colonization ( P = 0.65). No correlation was found between the etiologic factors and the decline of FEV1 . A correlation existed only between the first FEV1 and the decline of FEV1 (for the first FEV1 %, P = 0.038 [R = −0.17]; for the first FEV1 [mL] P = 0.026 [R = −0.18]). Conclusions: An annual mean FEV1 loss of 39 mL was found in adult patients with noncystic fibrosis bronchiectasis. The annual mean FEV1 decline was found to be associated with the baseline FEV1 value. Physicians should exercise caution in this regard in patients with bronchiectasis with low FEV1 values.